A study of a non‐conventional evaluation of results from salt spray test of aluminum High Pressure Die Casting alloys for automotive components. Issue 1 (27th July 2018) - Cecchel, Silvia; Cornacchia, Giovanna; Gelfi, Marcello
Abstract : Aim of the present work was to investigate in a non‐conventional way the results of aluminum castings salt spray tests. These experiments were engineered in order to obtain a quantitative measurement of the corrosion rate, instead of the qualitative visual analysis usually employed in the traditional salt spray test. These tests were performed on aluminum EN AC‐46000, EN AC‐44400, and EN AC‐43500 samples. A comparison was made with electrochemical tests on specimens and the traditional salt spray testing on a real dimension component. The results showed a good reliability of the new method that gave outputs in agreement with the electrochemical technique. The new concept of salt spray test data processing was able to detect very small differences in corrosion behavior of tested alloys, demonstrating higher precision and reliability in respect to the polarization technique. Such result was explained considering the adoption of specimen with larger area and longer time of exposure to the selected corrosive environment that reduce respectively the effect of uneven distribution of porosity and intermetallics in the samples, typical of aluminum castings, and the potential local and transient events related to these defects. Abstract : Corrosion rate data were obtained through engineered salt spray tests on aluminum casting samples. The results were compared with electrochemical tests on specimens and the traditional salt spray testing on a real size component. The new method showed a good reliability and a high accuracy.